National accounting scheme for biodiversity loss: An international trade perspective - Li, Xuemei; Xing, Lu; Zhang, Zhe; Zhang, Ying (Frontiers in Environmental Science, 2022)
International trade has emerged as a threat to biodiversity. Identifying the biodiversity loss in countries/regions driven by international trade is a prerequisite for effective protection. Considering the lack of existing research, it is urgently necessary to construct an equitable and reasonable accounting scheme for biodiversity loss. Therefore, based on the multi-regional input–output model framework, this study uses the International Union for Conservation of Nature Red List of Threatened Species data to evaluate and compare the biodiversity footprints of 188 countries/regions between 2006–2015. We find that the world’s biodiversity footprint is characterized by a significant spatial non-equilibrium driven by developed countries and developing countries with large economies. Financial intermediation and business activities, education, health, and other services, and construction and agriculture sectors play an important role in the accounting scheme for biodiversity and hence must be strictly controlled. This study will help construct a biodiversity conservation framework in the 2020s.